Design of Experiment to Reduce Waste in Chrome Coated Mirror - ริดเขียว ปิยพงษ์ (Frontiers in Engineering Innovation Research, 2012)
The chrome coated mirror process is one part of industrial of motor vehicle production. Most problems in case study of chrome coated mirror production are high waste during processing. Furthermore, quality of chrome coated mirror products has effect from unstable production during processing and has defect such as scratch on mirror surface, incomplete paint, small sport on mirror surface. As to reduce the waste and improve quality development of chrome coated mirror processing by experiment design such as Alternative DOE and Classic DOE method. By applying Alternative DOE can reduce the quantity of experiment as Taguchi’s method. For Classic DOE, increase the reliability of experiment by analyze as one-way ANOVA. From the result of case study show that the most effect to occur waste is pushcart factor and next effect is prevent dust on conveyor belt factor. Another effect to quality is chrome coating time. The best solution from the result of case study of reduce waste and improve quality is baking at 690 degree Celsius with conveyor belt speed of 15m per minute. Conclusion is use pushcart format with gap design, use plastic protection to make glass edge smooth, use air pressure in conveyor belt to prevent dust and chrome coating time 8 second.